2018
DOI: 10.3906/biy-1802-77
|View full text |Cite
|
Sign up to set email alerts
|

Exploring allosteric communication in multiple states of the bacterial ribosome using residue network analysis

Abstract: Antibiotic resistance is one of the most important problems of our era and hence the discovery of new effective therapeutics is urgent. At this point, studying the allosteric communication pathways in the bacterial ribosome and revealing allosteric sites/residues is critical for designing new inhibitors or repurposing readily approved drugs for this enormous machine. To shed light onto molecular details of the allosteric mechanisms, here we construct residue networks of the bacterial ribosomal complex at four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…The paper proposed that it could help to distinguish weak versus deleterious types of mutants. A more recent study defined the network using the phosphorus atom in the nucleotide and the alpha-carbon in the amino acid [6]. The centrality analysis highlighted how high betweenness centralities corresponded to an important functional role in allosteric communication pathways, implying that network analysis can reveal pathways between allosterically linked regions and possible targets for new antibiotics.…”
Section: Definition Of the Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper proposed that it could help to distinguish weak versus deleterious types of mutants. A more recent study defined the network using the phosphorus atom in the nucleotide and the alpha-carbon in the amino acid [6]. The centrality analysis highlighted how high betweenness centralities corresponded to an important functional role in allosteric communication pathways, implying that network analysis can reveal pathways between allosterically linked regions and possible targets for new antibiotics.…”
Section: Definition Of the Networkmentioning
confidence: 99%
“…Throughout this vast literature, the importance of connectivity has often been remarked and discussed, however, only a few papers have considered viewing the connections as a network. Some explorations considered using the nucleotides or amino acids as nodes and their interactions as edges [5,6], and showed that a network analysis highlights important mutations that have deleterious effects on ribosome function or highlighted highly conserved residues, drug binding sites and/or allosteric pathways. Other investigations considered interactions involving just ribosomal (r)proteins within each subunit [2,7] and revealed that the interactions are highly conserved [7].…”
Section: Introductionmentioning
confidence: 99%
“…In short, at each act of translation (elongation step), tRNA motion through the ribosome -translocation -is correlated with the motion of mRNA [2,3], large-scale conformational changes of tRNA [4] and ribosome [5][6][7][8][9], as well as chemical reactions -GTP hydrolysis in the translation factors [4] and amino acid addition to the growing polypeptide [10]. Synchronized action of distant parts of the ribosome and tRNAs implies the existence of some mechanism orchestrating them [11][12][13]. However, this allosteric mechanism remains unknown despite several decades of intensive studies of ribosome operation.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronized action of distant parts of the ribosome and tRNAs implies the existence of some mechanism "orchestrating" them [20][21][22]. Understanding of this mechanism is very important for molecular biology, since it would uncover the physics underlying the key life process; however, this mechanism remains unknown despite several decades of intensive studies of ribosome operation.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of this mechanism is very important for molecular biology, since it would uncover the physics underlying the key life process; however, this mechanism remains unknown despite several decades of intensive studies of ribosome operation. Several hypotheses on the nature of this mechanism synchronizing the ribosome operation have been suggested, most of them being of mechanistic character [20][21][22]. Note that such a mechanistic type of allostery (i.e.…”
Section: Introductionmentioning
confidence: 99%